Strategi Produser dalam Mempertahankan Eksistensi Program Buser SCTV - Nur Ridwan; Zakaria Satrio Darmawan (Syntax Idea)
This study aims to find out how the producer strategy management of the Buser program in SCTV keeps the program alive. This study, researchers used qualitative methods with a descriptive approach. This study uses the Concept of Program Strategic Management by Peter Pringle. The results of this study indicate that Buser's program producer strategic management in keeping the program running by ensuring four general steps - namely; program planning, program production, program implementation and program monitoring and evaluation - carried out well using strategies in writing scripts using non-standard terms or words that are not commonly used in script writing. These things can be seen by analyzing how the program is able to attract the attention of the public and the management strategies used by the producers of the program are able to maintain a high share and rating for the Buser program.